PEMBUATAN KECAP IKAN PETEK (Leiognathus splendens) SECARA FERMENTASI ENZIMATIS - Winarti Zahiruddin; Heni Sri Septiani; Pipih Suptijah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2010)
Fish sauce is one of fish-based processed food or fishery product from fermentation process. The appearance of fish sauce is clear brown liquid and it has unique taste and flavor so many people use this as addition ingredient or spices in food to increase its taste. In this study fish sauce was made from petek fish (Leiognathus splendens) that has slow economic value and has not been used optimally. Pineapple was also added as source of bromelin enzyme. This study consisted of two phases which were pilot study and main study. In pilot study fish sauce was made by adding tempe concentration from 10%, 20%, and 30%. Then organoleptic test was done to determine the best fish sauce. The result showed that the most favorablefish sauce was made by adding 10% of tempe concentration. The characteristics of this product were as follows: the color of fish sauce was yellowish brown, its flavor was almost smelled like tempe, its taste was almost salty and its appearance was clear. In main study, tempe concentration was reduced to 5%, 10% and 15%. Organoleptic test showed that the best product was petek fish sauce by adding 15% tempe concentration. The characteristics of this fish sauce were: its color was yellowish brown, its flavor was almost smelled like tempe, its taste was almost tasty and its appearance is clear. The best petek fish sauce had 72,34% water concentration, 6,40% protein, 20,67% ash, 0,36% fat and 0,23% carbohydrate.Keywords: enzyme fermentation, fish sauce, organoleptic test, petek fish, tempe